Bipolar Mood State Reflected in Functional Connectivity of the Hate Circuit: A Resting-State Functional Magnetic Resonance Imaging Study - Fan, Zebin; Yang, Jie; Zeng, Can; Xi, Chang; Wu, Guowei; Guo, Shuixia; Xue, Zhimin; Liu, Zhening; Tao, Haojuan (Frontiers in Psychiatry, 2020)
Background: Previous studies suggested bipolar disorder had an aberrant alteration in insular, putamen, and left superior frontal gyrus, which are the main components of the hate circuit. However, the relationship between hate circuit and the pathophysiologic substrate underlying different phases of the bipolar disorder remain unclear. In this study, we aimed to identify group differences of resting-state functional connectivity within the hate circuit in healthy controls (HCs) and bipolar patients in different mood states. Methods: Resting-state functional magnetic resonance imaging of the brain were acquired from 54 HCs and 81 patients with bipolar disorder including 20 with bipolar mania (BM), 35 bipolar depression (BD), and 26 bipolar euthymia (BE). We selected bilateral insula (L.INS and R.INS), bilateral putamen (L.PUT and R.PUT), and left superior frontal gyrus (L.SFGd) as seed regions, and conducted the seed-based functional connectivity analysis to identify group differences of connectivity strength within the hate circuit. Spearman correlations were performed to evaluate the relationship between the hate circuit and manic/depressive symptoms. Results: Significant group differences of connectivity strength within the hate circuit were found in connections of R.INS-L.SFGd, R.PUT-L.SFGd, and L.INS- R.PUT after false discovery rate corrected. BM group showed opposite hate circuit pattern to BD, BE, and HCs. BD group showed decreased hate circuit connectivity in the L.INS-R.PUT compared with the BE group. No significant difference was detected among BD, BE, and HCs. Furthermore, functional connectivity of the R.INS-L.SFGd and R.PUT-L.SFGd were positively correlated with manic symptoms, while, the L.INS- R.PUT was negatively correlated with depressive symptoms. Conclusions: Our preliminary findings suggest that altered functional connectivity of the hate circuit in different mood phases may be related to state markers and underpinning the neuropathological basis of bipolar disorder.